Deconstruction of Interhospital Transfer Workflow in Large Vessel Occlusion: Real-World Data in the Thrombectomy Era. Issue 7 (July 2017) - Ng, Felix C.; Low, Essie; Andrew, Emily; Smith, Karen; Campbell, Bruce C.V.; Hand, Peter J.; Crompton, Douglas E.; Wijeratne, Tissa; Dewey, Helen M.; Choi, Philip M.
Abstract : Background and Purpose—: Interhospital transfer is a critical component in the treatment of acute anterior circulation large vessel occlusive stroke transferred for mechanical thrombectomy. Real-world data for benchmarking and theoretical modeling are limited. We sought to characterize transfer workflow from primary stroke center (PSC) to comprehensive stroke center after the publication of positive thrombectomy trials. Methods—: Consecutive patients transferred from 3 high-volume PSCs to a single comprehensive stroke center between January 2015 and August 2016 were included in a retrospective study. Factors associated with key time metrics were analyzed with emphasis on PSC intrahospital workflow. Results—: Sixty-seven patients were identified. Median age was 74 years (interquartile range [IQR], 63.5–78) and National Institutes of Health Stroke Scale 17 (IQR, 12–21). Median transfer time measured by PSC-door-to-comprehensive stroke center-door was 128 minutes (IQR, 107–164), of which 82.8% was spent at PSCs (door-in-door-out [DIDO]; 106 minutes; IQR, 86–143). The lengthiest component of DIDO was computed-tomography-to-retrieval-request (median 59.5 minutes; IQR, 44–83). The 37.3% had DIDO exceeding 120 minutes. DIDO times differed significantly between PSCs ( P =0.01). In multivariate analyses, rerecruiting the initial ambulance crew for transfer ( P <0.01) and presentation during working hours ( P =0.04) were associated with shorter DIDO times. Conclusions—: In a metropolitan hub-and-spoke network, PSC-door-to-comprehensive stroke center-door and DIDO times are long even in high-volume PSCs. Improving PSC workflow represents a major opportunity to expedite mechanical thrombectomy and improve patient outcomes. Abstract : Supplemental Digital Content is available in the text.